The effect of ego depletion on arousal of elite iranian swimmers - Mehri, S.; Pooraghaei Ardekani, Z.; Khabiri, M. (Annals of Applied Sport Science, 2016)
The purpose of the present study is to examine the effects of ego depletion on arousal of elite Iranian swimmers. The sample comprised elite swimmers invited to the national swimming team as focused and semi focused (36 subjects). The research design was as pre- and post-test—in two phases of ego depletion conditions and the lack of ego depletion conditions in two experimental and control groups. The arousal was measured by a biofeedback device, and Stroop test was conducted in order to create ego depletion conditions. The results showed that ego depletion had no effect on the arousal of elite swimmers. In other words, the results showed that depletion of strength sources of self-control had no effect on elite swimmers` arousal. The findings—based on the theory of community facilities and the self-control model—showed that arousal is actually an accelerator and moderator of using self-control sources; it is not a factor using self-control sources and, also, ego depletion is not involved in arousal changes.